The Strategies of diplomacy in the Sirah of Prophet Muhammadﷺ; A True policy Maker - Saeed Ur Rehman, Dr. Muhammad; Ruby, Dr. Nayab (Al-Amīr Research Journal for Islamic Studies, 2023)
The strategies of diplomacy in the Sirah (biography) of Prophet Muhammadﷺ are multifaceted and offer timeless lessons in effective negotiation, conflict resolution, and international relations. Prophet Muhammad ﷺ was true policy maker and organized Diplomat. The present study shows about strategies which adopted by prophet ﷺ. The suggested study is circled into the historical and social perspective of seerah. Prophet Muhammad ﷺ completed his commitments and pacts. He was actually the leader of whole world. The Seerah history tells us the real and true position of prophet ﷺ. This article will explore key diplomatic approaches employed by the Prophetﷺ, including treaty-making, mediation, and communication, demonstrating their relevance in contemporary diplomatic practices. It will also highlight the Prophet'sﷺ emphasis on justice, empathy, and compassion as foundational principles in fostering peaceful relations and resolving conflicts, serving as a model for diplomatic engagement in today's world. The recommended research already the background of comparative analysis under the contemporary issues in which we can solve the problems through the Seerah history. Keywords; Conflict Management, Diplomacy, Seerah, Islamic Thought.